La numérisation des dispositifs de participation de la Mairie de Paris - Nicolas Douay (Netcom)
This article proposes a study of the uses of digital in the participative local processes using the socio-technical devices of participatory budget developed by the city of Paris. This approach “through instruments” is therefore aimed at studying the design, uses and effects of these instruments of participation. Our question is thus to deconstruct the impact of digital in the definition and appropriation of a new offer of participation. This approach has a dual dimension: on the one hand technical, by questioning the “participatory design” of the device in its hybrid dimension (digital / non-digital) and on the other, by analyzing the uses and effects generated. The case of Paris illustrates the emergence of digital as a new repository, at least in speeches, for the implementation of any participatory approach. The case of participatory budget thus appears to be the most advanced mechanism and refers to an evolution of the posture of the city of Paris which engages a little more in the participatory turn. In this perspective, the contribution of digital is not necessarily always quantitative by reaching a wider but rather qualitative audience by allowing a more continuous process and more constructed exchanges. However, the risk is that these digital instruments will not respond to the challenge of diversifying the public involved in the participation process.